Postmethod Pedagogy in Arabic-Speaking Instruction: A Contextual Case Study in an Indonesian Modern Islamic Boarding School - Abdul Muid; Bisri Mustofa; Faisal Mahmoud Adam; Mamluatul Hasanah; Muassomah Muassomah; Zakiyah Arifa (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
This study arises from the need to understand the learning of speaking skills in a more contextual way within the Modern Islamic Boarding School environment, given that previous studies still tend to highlight only the partial effectiveness of language methods or programs. This study aims to analyze how the learning strategy for speaking skills at Darul Qiyam Kerinci Modern Islamic Boarding School is constructed and implemented within the framework of postmethod pedagogy, particularly through the parameters of particularity, practicality, and possibility. The research uses a qualitative approach with a case study design. The subject of this study is the practice of learning Arabic Speaking skills in the pesantren environment, while the informants are the teachers of the boarding school who are directly involved in teaching Arabic and developing the language environment, who are purposively selected for their active involvement and willingness to participate. Data were collected through semi-structured interviews, observations, and document analysis, and then analyzed using thematic analysis. The results of the study show that speaking learning strategies are constructed contextually through the language environment, teachers' pedagogical reflections, and layered language practices. This strategy not only strengthens students' Speaking skills, but also shapes their courage, linguistic agency, and social identity. The practical implication of this study is that speaking skills instruction needs to be designed holistically by connecting language policy, authentic communicative practice, and the teacher’s role as a reflective practitioner.